2009
DOI: 10.1163/156921009x413199
|View full text |Cite
|
Sign up to set email alerts
|

The Culture of Indian Migration: A Theoretical and Empirical Analysis of Orissa and Rajasthan (1803-2003)

Abstract: A signifi cant segment of internal migration in India at large, and in the states of Rajasthan and Orissa in particular, continues to be distress-led. Colossal collapse of rural employment generation, the economic setbacks at cultivation, and, the largely defi cient employment opportunities in urban centres among others, are believed to be the driving force behind the rise of a more insecure type of movement now. Paradoxically however, this movement occurs in a world supplemented by a renewed belief in sanctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In contrast, authors found random migration affected cities adversely; Bhatt (2009) and Dubey and Palmer-Jones (2006) emphasized diversified environmental impacts: pollution, water sanitation, etc. Yigitcanlar and Dizdaroglu (2015) show that sudden migration is influenced by asymmetrical events (political uncertainty, ease of transfer, terrorism, etc.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, authors found random migration affected cities adversely; Bhatt (2009) and Dubey and Palmer-Jones (2006) emphasized diversified environmental impacts: pollution, water sanitation, etc. Yigitcanlar and Dizdaroglu (2015) show that sudden migration is influenced by asymmetrical events (political uncertainty, ease of transfer, terrorism, etc.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The planned development enhances society, economy and environment of the city and how it attracts migrants is highlighted by several authors: Gill (2003) and Seth et al (2009) in India; Faria et al (2017) in Nigeria; Rosenthal and Strange (2004) and Hossain (2001) in the USA; Bengston et al (2004) in Europe; Bhatt (2009) and Patil (2020) in China; and Kumar and Singh (2014) in Bangladesh. The studies found planned development accommodates better education and health-care systems, robust energy systems, reduce pollution, improved employment opportunities and infrastructure.…”
Section: Dynamic Interaction Of Rural-urban Migration and Urban Devel...mentioning
confidence: 99%
See 1 more Smart Citation
“…HEP, SUSIs differ significantly from one another. The indicators have been developed for India (Bhatt, 2009; Kumar and Singh, 2014; Roy and Roy, 2020b), Nepal (Gautam and Karki, 2004), the United States (Kaunda et al. , 2012), Europe (Bengston et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…HEP, SUSIs differ significantly from one another. The indicators have been developed for India (Bhatt, 2009;Kumar and Singh, 2014;Roy and Roy, 2020b), Nepal (Gautam and Karki, 2004), the United States (Kaunda et al, 2012), Europe (Bengston et al, 2004;Zelenakova et al, 2013), China (Frenkel, 2004;Liang et al, 2018) and Bangladesh (Goldman and Crow, 1996;Perveen et al, 2017a) around social, economic, environmental and institutional areas. Although several indicators are often considered individually or even in pairs, few studies have integrated several dimensions simultaneously (Pope et al, 2004;Roy and Thangaraj, 2021;Ugwu et al, 2006a).…”
Section: Sustainable Hydroelectric Power Project Planningmentioning
confidence: 99%